Answer: 1) Let's simplify step-by-step.
x22(x+y)−y2
Distribute:
=(x22)(x)+(x22)(y)+−y2
=x23+x22y+−y2
Answer:
=x23+x22y−y2
2)Let's simplify step-by-step.
x4+x2y2+y4
There are no like terms.
Answer:
=x4+x2y2+y4
Answer:
See explanations below
Step-by-step explanation:
a) 1/4+5/4
= (1+5)/4
= 6/4
= 3/2
b) 23/17+11/17
= (23+11)/17
= 34/17
= 2
c) 16/93+15/93
= (16+15)/93
= 31/93
= 1/3
d) 11/14+23/14
= (11+23)/14
= 34/14
= 17/7
e) 3/16+15/16
= (3+15)/16
= 18/16
= 9/8
f) 1 1/8 + 1 3/8
= 9/8 + 11/8
= (9+11)/8
= 20/8
= 5/2
g) 1 3/10+3 1/10;
= 13/10+31/10
= (13+31)/10
= 44/10
h) 2 3/5+3 2/5
= 13/5+17/5
= (13+17)/5
= 30/5
= 6
Answer:
the forth one is linear
Step-by-step explanation:
Answer:
what are you doing here honey and what is this gonna be about me in a hurry for the first two
Easy Algebra question!
Let's use "x" as a variable.
The equation would be x+x+60 = 240 with "x" being George's weight.
Subtract 60 from both sides and you get 2x = 180.
From there you divide both sides by 2, getting x=90.
"x" is George's weight, so he weighs 90 pounds.
ANSWER: 90 POUNDS